What uh the Folks Who Did this Survey Found: Expert Attribution in Spoken Academic Lectures - Ädel, Annelie (Nordic Journal of English Studies, 2008)
Academic writing has been said to display a tension between originality and humility to the community (Myers 1990; Berkenkotter & Huckin 1995; Hyland 1999). One of the fundamental ways in which this tension plays out is in references to previous research, or ‘attribution’. While recent research has emphasized the importance of attribution in academic writing—Hyland (1999), for example, found the average number of citations in research articles to be as high as 70 per 10,000 words—the role of attribution in spoken academic discourse is relatively uncharted territory. In this study of attribution in academic speech, transcripts of 30 large lectures from the Michigan Corpus of Academic Spoken English (MICASE; Simpson et al. 1999) were analysed, totalling 250,000 words. References to expert sources in the academic domain were analysed, specifically third person attribution (including third person pronouns, proper names, and a selection of nouns), as in “um and, Marx points out that those are the tools that the proletariat are gonna use”. The research questions were: To what degree do lecturers situate intertextually the knowledge and facts they are presenting? Do the disciplinary differences found in written citation practices also occur in speech? How variable are the formal realizations of attribution in speech? Contrary to previous research findings (e.g. Biber 2006; Swales 2005), the study showed both that expert attribution is quite pervasive and that there is disciplinary variation in academic speech. The findings are compared to studies of attribution in academic writing (e.g. Hyland 1999; Tadros 1993), with the goal of contributing to current research on the commonalities that academic speech (lectures) exhibits with academic writing on one hand, and non-academic speech on the other.